AMS Annual Meeting in Boston samt ASA Annual Meeting in Bloomington - Broman, Per F. (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1998)
AMS Annual Meeting in Boston, 29 oktober-1 november, 1998 ASA Annual Meeting, 4-7 november 1998, Bloomington